Short-term glucocorticoid administration in patients with protracted and chronic gout arthritis. Part 2 — comparison of different medication forms efficacy - A A Fedorova; V G Barskova; LA Yakunina; V A Nasonova (Научно-практическая ревматология, 2008)
Objective. To compare efficacy of different glucocorticoid (GC) medication forms in protracted and chronic gout arthritis. Material and methods. 59 pts with tophaceous gout (crystal-verified diagnosis) and arthritis of three and more joints lasting more than a months in spite of treatment with sufficient doses of nonsteroidal anti-inflammatory drugs were included. Median age of pts was 56 [48;63], median disease duration — 15,2 years [7,4;20], median swollen joint count at the examination — 8 [5; 11]. The patients were randomized into 2 groups. Methylprednisolone (MP) 500 mg/day iv during 2 days and placebo im once was administered in one of them, betamethasone (BM) 7 mg im once and placebo iv twice — in the other. Results. Number of pts with full resolution of arthritis, recurrent exacerbation, insufficient arthritis resolution or clinically insignificant response was comparable in both groups. More rapid decrease of pain at moving was achieved during the first 2-3 days after GC administration in pts with full resolution of arthritis (p=0,03) in group receiving MP in comparison with BM. At day 14 joint damage measures did not differ between groups. Conclusion. Efficacy of short-term glucocorticoid administration does not depend on mode of administration and GC medication form (methylprednisolone 500 mg/day iv during 2 days or betamethasone 7 mg im once.